2016
DOI: 10.1007/s13197-016-2406-6
|View full text |Cite
|
Sign up to set email alerts
|

Screening and purification of catechins from underutilized tea plant parts and their bioactivity studies

Abstract: Comparative investigation of major phytoconstituents was performed from various parts of tea plant viz. apical bud, subtending 1st-5th leaf, stem, coarse leaves, flowers, fruits and roots. From the results of comparative RP-HPLC-DAD analysis it was found that underutilized tea parts especially coarse leaves, flowers and fruits contains abundant amount of phenolics (17.5%) and catechins (4-5%). From these underutilized tea plant parts the catechins were extracted and purified and then screened for their antican… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Most of the reported studies were performed with plant leaves; however other plant parts revealed to possess antimicrobial activity. Namely, Rana et al [ 64 ] evaluated the activity of catechins from underutilized tea plant parts (coarse leaves, flowers and fruits) against Gram positive and Gram negative food-borne pathogens ( B. subtilis , S. aureus, E. coli and Klebsiella pneumoniae ). The best result was obtained for tea flower extract (maximum zone of inhibition at 20 mg/mL) against S. aureus and K. pneumonia .…”
Section: Antimicrobial Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the reported studies were performed with plant leaves; however other plant parts revealed to possess antimicrobial activity. Namely, Rana et al [ 64 ] evaluated the activity of catechins from underutilized tea plant parts (coarse leaves, flowers and fruits) against Gram positive and Gram negative food-borne pathogens ( B. subtilis , S. aureus, E. coli and Klebsiella pneumoniae ). The best result was obtained for tea flower extract (maximum zone of inhibition at 20 mg/mL) against S. aureus and K. pneumonia .…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…The antiproliferative activity of the methanolic extract was examined and the results showed a powerful growth inhibition of both cell lines in a concentration-dependent manner (IC 50 = 54 ± 10 for A-498 and 129 ± 28 µg/mL for 769-P cells) It should be noted that, along with the antitumor activity studies, the authors identified the extract phenolic and methylxanthine content allowing a deeper knowledge on the compounds responsible for the reported biological activity. In 2016, Rana et al [ 64 ], evaluated the bioactivity (including the antitumor against oral cancer cells) of frequently neglected tea plant parts as apical buds, stem, coarse leaves, flowers, fruits and roots. The results showed that tea fruit extract exhibited higher toxicity (71.6 to 74.9% at the concentration of 50–200 µg/mL) against oral cancer cells being comparable to the obtained with standard vinblastibe (74.2% at 2 µg/mL concentration).…”
Section: Antitumor Activitymentioning
confidence: 99%
“…Flavonoids are formed into their derivatives such as flavonoid glycoside through methylation and galactosylation. The majority of polyphenols are located in the leaves of the tea plant; however, some of them distribute to the flower and fruit …”
Section: Metabolic Characteristic Of Principle Metabolites In Teamentioning
confidence: 99%
“…The majority of polyphenols are located in the leaves of the tea plant; however, some of them distribute to the flower and fruit. 72 Metabolism of Theanine. There are 26 amino acids identified in tea, including 20 protein amino acids and six nonprotein amino acids.…”
Section: Metabolites In Teamentioning
confidence: 99%
“…A well diffusion method was used to evaluate the antimicrobial activity of citrus fruit juices, following procedure as discussed in Rana et al (2016). Nutrient broth was used for the growth of bacterial culture.…”
Section: Well Diffusion Methodsmentioning
confidence: 99%